The Effect of Providing Educationresearch Services by Founding a Clinical Research Development Center on the Research Performance of Clinical Faculty Members of Kerman University of Medical Sciences - Hamid Najafipour; Sodaif Darvish Moghadam; Jalal Azmandian; Hamed Hosseini (Kerman University of Medical Sciences, 2010)
Background & Objective : Evaluating research indicators amongst clinical and basic science faculty members reveals that such indicators are lower in clinical faculty members Hence we decided to assess the effect of providing educationresearch services by founding a clinical research development center on the research performance of clinical faculty members of Kerman University of Medical Sciences   Methods : In this intervention field study 66 faculty members of Afzalipour teaching hospital and 45 ones in Shafa teaching hospital were recruited as cases and controls respectively After founding the research center in cases work place educationresearch services were provided for two years The research activities of cases and controls were compared two years before and two years after founding the center   Results : 39 and 33 percent increase were observed in the cases total and per capita number of published articles respectively similar indicators showed 21% and 216% decrease in the controls accordingly The differences between two groups regarding both indicators were significant (P